Competition universalism: historical origins and timely alternatives - Claudius Gräbner; Stephan Pühringer (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2021)
This paper discusses the actual relevance and historical origins or 'competition universalism'. In economics, competition is conceptualized as a nearly ubiquitous element of societies, or, at least, used to study a wide array of social and political relations, including competition between firms for market shares, between individuals for prestige, countries for resources, athletes for victory, or politicians for influence. This trend towards 'competition universalism' was facilitated by the increasing dominance of an economic approach that places less weight on descriptive accuracy and a consideration so socio-historical specificities, but instead focuses on the development of general and tractable mathematical models. Thereby, the paper links the trend to competition universalism to developments in the epistemological orientation in economics. It first explicates the historical genesis of competition universalism, then discusses the extent it has reached today, and concludes with critical remarks and the proposition of an alternative, more particularist approach to study competition.
Keywords: B0; B4; Z1; 330; competition universalism; economic and social sphere; economic imperialism; economic methodology